Shaoyao-Gancao Decoction Promoted Microglia M2 Polarization via the IL-13-Mediated JAK2/STAT6 Pathway to Alleviate Cerebral Ischemia-Reperfusion Injury - Lu, Juanjuan; Wang, Jie; Yu, Long; Cui, Rong; Zhang, Ying; Ding, Hanqing; Yan, Guofeng (Mediators of Inflammation, 2022)
Microglia in the penumbra shifted from M2 to M1 phenotype between 3 and 5 days after cerebral ischemia-reperfusion, which promoted local inflammation and injury. Shaoyao-Gancao Decoction (SGD) has been found to result in a significant upregulation of IL-13 in the penumbra, which has been shown to induce polarization of M2 microglia. There was thus a hypothesis that SGD could exert an anti-inflammatory and neuroprotective effect by activating IL-13 to induce microglia polarization towards M2 phenotype, and the purpose of this study was to explore the influence of SGD on microglia phenotype switching and its possible mechanism. Rats who received middle cerebral artery occlusion surgery (MCAO) were treated with SGD for 3 or 6 days, to investigate the therapeutic effect and the underlying mechanism of SGD for cerebral ischemia-reperfusion injury (CI/RP). The results indicated that SGD improved neurobehavioral scores and reduced apoptosis. Furthermore, SGD significantly decreased M1 microglia and M1-like markers, but increased M2 microglia and M2 markers. Moreover, higher levels of IL-13 and ratios of p-JAK2/JAK2 and p-STAT6/STAT6 were found in the SGD group compared to the MCAO. In conclusion, it was verified that SGD prevented injury by driving microglia phenotypic switching from M1 to M2, probably via IL-13 and its downstream JAK2-STAT6 pathway. Given that no further validation tests were included in this study, it is necessary to conduct more experiments to confirm the reliability of the above results.